New species of Nectria and Thyronectria from Xinjiang, China - Ma, Rong; Li, Sheng-Nan; Zhao, Ying; Wang, Min; Michailides, Themis J.; Tian, Cheng-Ming (Phytotaxa, 2020)
Nectria berberidis sp. nov. and Thyronectria berberidicola sp. nov. isolated from Berberis heteropoda in Xinjiang Uygur Autonomous Region, China, are described and illustrated. Nectria berberidis is characterized by clavate asci (50–87 × 8–12 μm) with ellipsoidal to fusiform, 1-septate ascospores. Thyronectria berberidicola is characterized by clavate asci (117–25.9 × 63.7–117.9 μm) with ellipsoidal to fusiform ascospores that have 5–8 transverse septa and 1(–2) longitudinal septum. Ascospores bud to produce hyaline, bacillar ascoconidia. Phylogenetic analyses based on alpha-actin (ACT), the internal transcribed spacer (ITS), the large nuclear ribosomal RNA subunit (LSU), translation elongation factor 1-alpha (TEF1) and the β-tubulin (TUB) sequence data revealed that isolates of N. berberidis and T. berberidicola form a distinct clade within Nectria and Thyronectria, respectively. In addition, Nectria nigrescens is reported for the first time in China.